2020
DOI: 10.1038/s41598-019-57193-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregates stability and storage of soil organic carbon respond to cropping systems on Black Soils of Northeast China

Abstract: Monoculture and improper management may reduce soil fertility and deteriorate soil structure in Black soils (Mollisols) of Northeast China. The experiment was carried out from 2015 to 2016 in Black Soils comprising five cropping systems: continuous corn (CC), soybean-corn rotation (SC), cornsoybean rotation (CS), fallow-corn (FC), and fallow-soybean (FS). Our results showed that CS and FS treatments significantly increased mean weight diameter (MWD) and fractal dimension (D) in mechanical stability aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 78 publications
5
53
2
Order By: Relevance
“…This may be a consequence of variations in SOM and lability under the different plant species, as a consequence of the aforementioned differences in rooting morphology and root exudate chemistry in both these plant species, compared to Lp, as such differences have been reported to influence both the Planctomycetes (Buckley et al., 2006) and the Bacteroidetes (Fierer et al., 2007). The alterations in SOM chemistry induced by a legume may also alter the size distribution of soil aggregate fractions (Zhou et al., 2020). Such a process may explain the difference in the abundance of the Gemmatimonadetes between Tp and Lp, as this phylum has been reported to be quite abundant in the inner micro‐aggregate (Mummey, Holben, Six, & Stahl, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This may be a consequence of variations in SOM and lability under the different plant species, as a consequence of the aforementioned differences in rooting morphology and root exudate chemistry in both these plant species, compared to Lp, as such differences have been reported to influence both the Planctomycetes (Buckley et al., 2006) and the Bacteroidetes (Fierer et al., 2007). The alterations in SOM chemistry induced by a legume may also alter the size distribution of soil aggregate fractions (Zhou et al., 2020). Such a process may explain the difference in the abundance of the Gemmatimonadetes between Tp and Lp, as this phylum has been reported to be quite abundant in the inner micro‐aggregate (Mummey, Holben, Six, & Stahl, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A significantly improved soil aggregate stability, observed in the L–R–R than in the M–R–R and W–R–R, suggested that inclusion of legumes (such as lentil) in managed cropping systems had beneficial effects on soil physical properties, aggregate formation, and stability ( Chu et al., 2016; Zhou et al., 2020). Our results were in agreement with other studies that reported that the type, amount, and C:N of biomass contribution under different cropping and residue management systems determine residue decomposition and microbial utilization to influence soil aggregate properties ( Paustian et al., 1997; Sainju et al., 2003; Tivet et al., 2013; Zhou et al., 2020). Moreover, residue that decomposes quickly produces transient and temporary binding agents that are responsible for macroaggregate formation, while slow decomposition releases more processed humic materials that are responsible for stable microaggregates ( Sun et al., 1995; Sisti et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the soils under continuous rice monocropping are currently facing a serious threat of accelerated soil and environmental quality degradation ( Zhou et al., 2020). Rice is a staple food for half of the global population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rotation treatments also increased the water-stable aggregates stability rate (WSAR), in addition to reducing the aggregates destruction (PAD) more than the CC treatment. Furthermore, rotation rather than CC treatments enhanced the percentage of macro-aggregates [208], thus suggesting that CC may negatively affect soil aggregation, aggregate stability, and the composition of aggregate-size classes. However, the impact of CC on soil structure may differ among crops.…”
Section: Soil Aggregation and Structurementioning
confidence: 98%
“…For instance, the continuous soybean cropping reduced the soil aggregate stability [207]. A recent study reported the impact of different cropping systems such as continuous corn (CC), soybean-corn rotation (SC), corn-soybean rotation (CS), fallow corn (FC), and fallow soybean (FS) on soil aggregates stability [208]. Their results showed that the CS and FS treatments significantly enhanced the mean weight diameter (MWD) and fractal dimension (D).…”
Section: Soil Aggregation and Structurementioning
confidence: 99%